2018
DOI: 10.1186/s12913-018-3066-1
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare resource use and economic burden attributable to respiratory syncytial virus in the United States: a claims database analysis

Abstract: BackgroundDespite several studies that have estimated the economic impact of Respiratory Syncytial Virus (RSV) in infants, limited data are available on healthcare resource use and costs attributable to RSV across age groups. The aim of this study was to quantify age-specific RSV-related healthcare resource use and costs on the US healthcare system.MethodsThis retrospective case-control study identified patients aged ≥1 year with an RSV event in the Truven Health Marketscan® Commercial Claims and Encounters an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 36 publications
0
51
1
Order By: Relevance
“…estimated 14,000 deaths per year in the United States (2). Hospitalization due to RSV is a major economic burden, especially in preterm infants and older adults (3).…”
mentioning
confidence: 99%
“…estimated 14,000 deaths per year in the United States (2). Hospitalization due to RSV is a major economic burden, especially in preterm infants and older adults (3).…”
mentioning
confidence: 99%
“…They found that higher annual costs in the RSV infants compared to the matched controls across all age groups; ranging from $7,535 to $40,405. 22 None of the well-appearing infants < 60 days of age with no sick contacts and respiratory symptoms tested positive for RSV. Although, RSV causes significant cost to healthcare, cost may be decreased by not testing this population for RSV/flu.…”
Section: Discussionmentioning
confidence: 94%
“…They found that higher annual costs in the RSV infants compared to the matched controls across all age groups; ranging from $7,535 to $40,405. 22 None of the well-appearing infants < 60 days of age with no sick contacts and respiratory symptoms tested positive for RSV. Although, RSV causes signi cant cost to healthcare, cost may be decreased by not testing this population for RSV/ u.…”
Section: Discussionmentioning
confidence: 94%